Rheum turkestanicum reduces glutamate toxicity in PC12 and N2a cell lines - Rajabian, Arezoo; Sadeghnia, Hamid-Reza; Moradzadeh, Maliheh; Hosseini, Azar (Folia Neuropathologica, 2018)
Glutamate is considered to be responsible for the pathogenesis of many neurodegenerative diseases. Reactive oxygen species (ROS) production is considered to be involved in the glutamate-induced apoptosis process. In this study, we investigated the neuroprotective effects of Rheum turkestanicum in the glutamate-induced rat pheochromocytoma (PC12 cells) and mouse neuroblastoma (N2a) cell lines. Rutin as an antioxidant was used as positive control. Glutamate cytotoxicity was accompanied by an increment of malondialdehyde (MDA) content, ROS generation and apoptosis induction. However, pretreatment with the root extract of R. turkestanicum signiﬁcantly reduced MDA content, ROS generation and apoptotic cell death. Also rutin at a dose of 100 µM reduced ROS production and protected against glutamate toxicity. Also the quantification of rutin in R. turkestanicum extract was achieved and was about 0.11% ± 0.01 w/w. All these ﬁndings indicated that R. turkestanicum protected PC12 and N2a cells against glutamate-induced oxidative cell death and apoptosis and might raise the possibility of R. turkestanicum usage as a neuroprotective agent.